ANALISIS FRAMING ROBERT N. ENTMAN PADA MEDIA ONLINE KOMPAS.COM TENTANG PEMBERITAAN TEWASNYA BRIGADIR J - Fahrika Tri Ramadhanti; Andri Maijar (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The subject matter of this thesis is the occurrence of a shootout among police officers at the home of Inspector General Ferdy sambo due to alleged harassment of his wife then became the news of all journalism platforms with various forms of processing by the media, so to identify the use of Robert N. Entman's framing analysis on KOMPAS.com online media related to the news of the death of